Kin-Dza-Dza - Kančeli, Gija Aleksandrovič 1935-2019 (Ruscico, 2005)
"Kin-dza-dza" is one of the strangest artefacts in all of Soviet cinema. It's a science fiction satire in which Vladmir and Gedevan, a gruff Russian construction worker and a Georgian student, find themselves accidentally transported to Pluke, a barren desert-world with a barbaric, bureaucratic society. Gradually realising that they are not in a "capitalist country", the two men begin a long and farcical voyage home that more closely resembles the theatre of the absurd than it does any preconceived notion of cinematic science fiction. [...]" [electricsheepmagazine.co.uk]
Internationale Filmfestspiele in Rio de Janeiro - Spezialpreis der Jury für die "Beste gestalterische Konzeption". - 1987: "Nika-87"-Preise an den Komponisten Gija Kantscheli und der Tonregisseurin Ekaterina Popowa
Orig.: Sowjetunion 1986
Enth. interview with director G. Daniela ; video subject "chatlian language"-short dictionary" ; filmographies ; photo album